Study of agglomeration and magnetic sedimentation of Glutathione@Fe3O4 nanoparticles in water medium (2018)
The study of the efficiency of the magnetic separation of nanoparticles in environment is important for its implementation in the remediation of water bodies. In this work the sedimentation dynamics of Glutathione@MNPs were evaluated for water systems with addition of calcium, zinc and sodium ions in a concentration range of 0-40 mg/L in the presence and absence of a vertical magnetic field of 0.2 T. Also, critical coagulation concentrations (CCC) were determined based on the DLVO theory. Particles stability in the absence of metal ions higher than 8 weeks could be observed, whereas in the presence of these ions the stability was reduced to 8 weeks. Separation of the material from the aqueous phase higher than 90% was obtained both for the presence of ions and for the material after the addition of heavy metals such as Hg and Cr.